Pengaruh Layanan Konseling Kelompok Strategi Self Compassion Untuk Mereduksi Stres Akademik - Adinia Putri Fadillah; Hadi Pranoto; Eko Susanto (Universitas Muhammadiyah Metro, 2026)
Academic stress is a condition caused by pressure related to educational demands which if not overcome can have a negative impact on students. This study aimed to determine the effect of group counseling services self compassion strategy in reducing the academic stress of students of SMK Negeri 3 Metro. The pretest results showed 6 out of 10 students experienced high academic stress. The research method used was an experiment with pre-experimental design in the form of one-group pretest-posttest design. The treatment given was group counseling services self compassion strategy for 3 meetings. Data analysis used paired sample t-test with the help of JAMOVI. The results showed a p value <0.001 and cohen's d = 3.28, which means there was a significant decrease in academic stress levels after receiving treatment. Overall, it can be concluded that group counselling service self compassion strategy had a positive effect in reducing the academic stress of students of SMK Negeri 3 Metro.